(untitled) (CHORNOMORSKI BOTANICAL JOURNAL, 2013)
Mycelium dikaryotic cultures of Sch. commune unlike monokariotic has almost twice the width of hyphae, formed colonies more dense with well-developed aerial and submerged mycelium are found. Electrophoretic studies endoenzymes systems allow us to identify dominant monokariotic culture with joint growth on the single substrate.